Composition of the Wild Rabbit Nest and Its Implication for Domestic Rabbit Breeding - Ágnes Bilkó; Imre Petróczi; Boróka Bárdos; István Nagy; Vilmos Altbacker (Applied Sciences, 2022)
Wild European rabbits (Oryctolagus cuniculus) give birth in an underground nursery burrow where the kits are hermetically closed into the nest chamber for several weeks except for the three minutes of daily nursing. Given this confinement, the nest quality seems to be crucial in affecting the kits’ survival. The situation is less critical in rabbitries where the domesticated descendants are kept and give birth in separate nest boxes where the temperature and humidity conditions are less extreme and nests consist of fur and wood shavings or straw. However, nesting behaviour of domestic does still reflects several aspects of the ancestors, and providing conditions close to their biological needs is advised. The present study aimed to understand the factors contributing to the nest material choice of rabbits by analysing the composition of wild rabbit nests and testing naive domestic does in controlled laboratory settings for their preferences in constructing their nests. We were able to collect 21 just abandoned nests in their natural habitat and found they contained rabbit fur and hay, of which 85% was dry grass, mostly long leaves of Calamagrostis sp. Using domesticated rabbit does, we then tested if there is a preference for the features of the wild rabbit nests or whether the above-mentioned finding was either an accidental consequence of grass availability or ageing of the nest material. Two-way choice tests revealed that primiparous domestic does preferred the dry grass over green and long leaves over short grass bunches for nest building. Ageing of the nest material was rather negligible and did not contribute to the high level of dry grass content. We concluded that long dry grass is recommended as it seems to fulfil basic needs of this domesticated animal.